2018
DOI: 10.1002/asl.811
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between convective bursts and the rapid intensification of Typhoon Mujigae (2015)

Abstract: Typhoon Mujigae was the strongest typhoon in 2015, and underwent an extreme rapid intensification (RI). The RI of Mujigae was reasonably reproduced by a 72‐hr control simulation. By enhancing two updrafts in the eye wall, connective bursts (CBs) were found to have played an important role in the formation of the two warming cores in the middle and upper troposphere, respectively, which triggered and maintained the RI of Typhoon Mujigae. Meanwhile, CBs induced the upper‐tropospheric potential vorticity anomaly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Based on the refined 72‐hr model output as presented by Tang et al . (), we studied the various inner‐core structures, distribution features and associated LH effects of different convection types classified from the pre‐RI to RI stage of Typhoon Mujigae. The main results can be summarized as follows: By comparatively analyzing the patterns and percentages of various convections, it is shown that the inner‐core precipitation evolved from a mix of convective–SP prior to RI to a predominance of CP as RI began.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the refined 72‐hr model output as presented by Tang et al . (), we studied the various inner‐core structures, distribution features and associated LH effects of different convection types classified from the pre‐RI to RI stage of Typhoon Mujigae. The main results can be summarized as follows: By comparatively analyzing the patterns and percentages of various convections, it is shown that the inner‐core precipitation evolved from a mix of convective–SP prior to RI to a predominance of CP as RI began.…”
Section: Resultsmentioning
confidence: 99%
“…For more details, please refer to Tang et al . (), in which we successfully reproduced the track and intensity of Typhoon Mujigae (2015) by using the WRF model (Figure in Tang et al, ).…”
Section: Model and Methodsmentioning
confidence: 99%
See 3 more Smart Citations